THE IMPACT OF GRAY PROFITABILITY INDEX AND PUBLIC OWNERSHIP ON FINANCIAL STATEMENTS DISCLOSURE WITH AUDIT COMMITTEE AS A MODERATING VARIABLE - Indraguna Kusumabrata (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2021)
Disclosure of financial statements is one of the most important measurements for a sustainable company. This study will examine the effect of IFRS implementation on the gray profitability index and the portion of public share ownership on the disclosure of financial statements with the audit committee as a moderating variable. This study uses a quantitative research model and uses secondary data. The data in this study used data analysis methods, namely Moderating Regression Analysis (MRA) with IBM SPSS software and Microsoft Excel program as a testing support system, with data analysis techniques presented in the form of a classic assumption test and R2, F test and T test. The population in this study were all property and real estate companies that consistently had complete financial and annual reports for 2018 to 2019. This study used a sampling technique, namely purposive sampling and obtained 32 companies according to the classified criteria. The results indicated that the gray profitability index had no effect on the disclosure of financial statements, as well as the addition of the audit committee as a moderator did not strengthen the relationship to the disclosure of financial statements. Furthermore, the variable share of public ownership has a positive and significant effect on the disclosure of financial statements, as well as the moderation of the audit committee which further strengthens the relationship with the disclosure of financial statements. Kata Kunci: Gray Profitability Index, Public ownership, Disclosure of financial statements, and Audit Committee. JEL Classification: G32, M41